ISSUES OF CHILDREN SPIRITUALITY IN CIRCLES IN OUT-OF-SCHOOL EDUCATION SYSTEM (Intent Research Scientific Journal, 2023)
This article discusses the issues of raising the morale of students in Barkamol Avlod children's schools operating in our republic. The article also provides more detailed information about the principles of spirituality, ethics and humanism. Examples of the activities of children's school clubs "Barkamol Avlod" are presented.